2018
DOI: 10.4102/hsag.v23i0.1166
|View full text |Cite
|
Sign up to set email alerts
|

Expected clinical competence from midwifery graduates during community service placement in Limpopo province, South Africa

Abstract: BackgroundThe implementation of community service for nurses commenced in January 2008 (Department of Health 2007) and was regulated by the South African Nursing Council (SANC) Regulation 765 of 24 August 2007 (SANC 2010). All nurses completed the 4-year nursing diploma or degree for registration as a nurse (General Community and Psychiatry) and as a midwife to 'practice a profession in a prescribed category' and to carry out 1 year of remunerated compulsory community service (Department of Health 2006). Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…This starts with being a novice, passing through an advanced beginner, competent and proficient before finally reaching the fifth stage of advanced competence. This process should be supported as shown by the work of Netshisaulu and Maputle ( 2018 ) who showed that as students lack confidence and skills to take up the new roles and accountability, role transition support and a foundation period of preceptorship for midwifery graduates at the start of their careers help midwives to make the journey from a novice to an expert (Netshisaulu & Maputle 2018 ). The authors also advocated that a contextual transition programme should be developed by institutions to orientate and mentor graduate midwives in their new roles before they could function as independent practitioners (Netshisaulu & Maputle 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This starts with being a novice, passing through an advanced beginner, competent and proficient before finally reaching the fifth stage of advanced competence. This process should be supported as shown by the work of Netshisaulu and Maputle ( 2018 ) who showed that as students lack confidence and skills to take up the new roles and accountability, role transition support and a foundation period of preceptorship for midwifery graduates at the start of their careers help midwives to make the journey from a novice to an expert (Netshisaulu & Maputle 2018 ). The authors also advocated that a contextual transition programme should be developed by institutions to orientate and mentor graduate midwives in their new roles before they could function as independent practitioners (Netshisaulu & Maputle 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study conducted by Netshisaulu and Maputle (2018) in the Limpopo Province, it was identified that new graduate midwives placed for community service lacked a sense of independence and commitment to patient care and could not perform delegated duties with respect to ward coverage as per the expectations of experienced midwives. This lack of independence and commitment was seen to have an impact on the increased workload and frustration of the experienced midwives supervising CSNs (Netshisaulu & Maputle 2018). Therefore, experiences of CSNs in the NWP regarding their clinical competence during placement need to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…NGRNs face several challenges when entering the practice environment after completing their studies. Typical challenges are lack of independence, low confidence and feelings of incompetence [ 3 , 4 ], thus, necessitating further investigation into the competencies nurses require to deliver quality patient care. As far as the authors could establish this was the first competency profile developed based on the perceptions of both nurse educators and final-year nursing students who were HCPs working within the clinical environment.…”
Section: Discussionmentioning
confidence: 99%
“…South African (SA) studies indicate that NGRNs have a lack of knowledge and skills, insufficient record keeping and are not following protocols [ 2 ], which again could be due to competency issues. Certain NGRNs show a lack of independence and confidence, as well as feelings of incompetence [ 3 , 4 ]. Further challenges were found to be: feeling overwhelmed and struggling with the transition from student to NGRN [ 5 ], insufficient practical experience as well as deficiencies and adequacies in their professional role [ 3 ].…”
Section: Introductionmentioning
confidence: 99%